Symbols and myth-making in modernity : deep culture in art and action - Tiaynen-Qadir, Tatiana; Qadir, Ali (Anthem Press, 2023)
'Symbols and Myth-Making in Modernity' unpacks the deep culture that nourishes human perception of reality through symbols. From ancient mythical creatures and rites through masterpieces of Renaissance to modern art and cinema, the book illustrates how ever-present cross-cultural symbols erupt in popular culture today, and what work they do in transforming the self and society.